2017
DOI: 10.14687/jhs.v14i2.4411
|View full text |Cite
|
Sign up to set email alerts
|

Examination of academic self-efficacy and motivation according to demographic characteristics of graduate education candidates (Cumhuriyet University example)<p>Lisansüstü eğitim adaylarının akademik öz-yeterlik ve güdülenmelerinin demografik özelliklerine göre incelenmesi (Cumhuriyet Üniversitesi örneği)

Abstract: The aim of this research is to examine the academic self-efficacy and motivation of candidates applying for the postgraduate education program of the Institute of Health Sciences according to the age, sex, graduated section and marital status variables. The sample of this research in the relational screening model is composed of 100 students who applied to the Physical Education and Sports Master program, which is included in the study by using appropriate sampling method. Academic Selfefficacy Scale and Acade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
(2 reference statements)
0
2
0
Order By: Relevance
“…The studies on the effect on academic motivation in the literature analysed academic motivation in terms of such different variables as gender, socio-economic status, and educational background. Studies that analyse the effect levels of gender on academic motivation by various variables are also found in the literature (Ertem, 2006;Gündüz, Şahin, and Önal, 2009;Hotaman, and Yüksel-Sahin, 2010;Bedel, 2013;Polat, 2013;Aktaş, 2017;Demir and Arı, 2013;Eroğlu, Yıldırım and Şahan, 2017;Özgül and Diker, 2017;Pala, 2019;).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…The studies on the effect on academic motivation in the literature analysed academic motivation in terms of such different variables as gender, socio-economic status, and educational background. Studies that analyse the effect levels of gender on academic motivation by various variables are also found in the literature (Ertem, 2006;Gündüz, Şahin, and Önal, 2009;Hotaman, and Yüksel-Sahin, 2010;Bedel, 2013;Polat, 2013;Aktaş, 2017;Demir and Arı, 2013;Eroğlu, Yıldırım and Şahan, 2017;Özgül and Diker, 2017;Pala, 2019;).…”
Section: Introductionmentioning
confidence: 96%
“…In this study, studies on the effect of gender on academic motivation were made on different fields of study. A study was found on the effect of gender on academic motivation which is focused on the students of faculty of education (Saracaloglu, 2008;Saracaloğlu, Kumral, and Kanma, 2009;Şahin and Çakar, 2011;Terzi, Mahmut, and Gürbüz, 2012;Demir and Arı, 2013;Özgül and Diker, 2017;Terzi, Uyangor, and Dulker, 2017;Titrek, Çetin, Kaymak, and Kaşikçi, 2018;Pala, 2019). A study was also found on the effect of gender on academic motivation which is focused on the students of faculty of theology (Aktaş, 2017;Yıldız, Sezen and Yenen, 2007).…”
Section: Introductionmentioning
confidence: 99%